Desain dan Implementasi Cron Gateway Berbasis Web Menggunakan PHP-CLI dengan Penyimpanan Berbasis JSON - Supriyanto, Joko; Wicaksono Yuli (Universitas Muhammadiyah Sorong, 2025)
Traditional cron configuration still relies on complex command-line interfaces (CLI), which are error-prone and lack integrated monitoring. This makes it difficult for administrators, especially those less skilled with shell commands. Cron Gateway is an application that simplifies and centralizes the management of Linux cron jobs by providing a visual and interactive web interface as a replacement for text commands in the command-line. The web-based Cron Gateway, developed with PHP, separates the management interface (web UI) from the execution engine (CLI). Configurations are stored in a single centralized JSON file, making it portable without requiring an external database. The system supports hybrid scheduling (simple intervals & cron format) and provides a parser to translate cron expressions into natural language in real time. Testing Cron Gateway on the application https://kaldik.sibermu.ac.id demonstrated that it can run asynchronous tasks to send activities to Google Calendar at 10-second intervals more than 15,300 times, execute auto synchronization of Google Calendar submissions at 10-second intervals more than 4,753 times, and send event schedules to 4,399 students. It executed log deletion processes scheduled once daily at 00:00 twice, and ran daily AI-generated summaries for the academic calendar at 00:01 twice—all stably. The application reliably performs daily tasks on time as scheduled. All tasks were logged as